Influence of socio-demographic and environmental factors on child mortality in India - Panda, Snigdha; Sarangi, Pravat Kumar (International Journal Of Community Medicine And Public Health, 2023)
Background: According to National Family Health Survey (NFHS) report (round 5), under five child mortality rate is 42 per 1000 live births which is far behind the sustainable development goal and National Health Policy, 2017. This research work aims to investigate the socio-demographic and environmental risk factors associated with child mortality between age 0-59 months in India. Methods: To analyse the objective of this study secondary data of NFHS round 5 are used. NFHS is a large scale, multi-rounds survey conducted by ministry of Health and Family Welfare (MoHFW) with the collaboration of International Institute for Population Sciences (IIPS), Mumbai. Cox regression model is used for the statistical analysis and the data analysis work is carried out using R software. Results: The research found that mortality rate is higher among mother’s age less than 20 years and mother’s having no education. In rural areas mortality rate is high compared to urban residence. Birth order of child more than 6 has 2.0966 times higher risk to die and the male child is more likely die than the female. Children born to family having richest wealth index (HR=0.6550, CI: 0.5856-0.7327) has the least mortality rate. Use of polluting cooking fuel and unimproved sanitation facility increase death risk on under-five mortality 1.1334 times and 1.0905 times respectively. Conclusions: The study found a strong influence of socio-demographic and environmental factors on child mortality under the age of five.